2017
DOI: 10.1080/03081087.2017.1295433
|View full text |Cite
|
Sign up to set email alerts
|

Biderivations of finite-dimensional complex simple Lie algebras

Abstract: Abstract. In this paper, we prove that a biderivation of a finite dimensional complex simple Lie algebra without the restriction of skewsymmetric is inner. As an application, the biderivation of a general linear Lie algebra is presented. In particular, we find a class of a non-inner and non-skewsymmetric biderivations. Furthermore, we also get the forms of linear commuting maps on the finite dimensional complex simple Lie algebra or general linear Lie algebra.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…A mapping φ of a Lie algebra g is called commuting if [φ(x), x] = 0 for any x in g (see [2]). An important application of linear commuting mappings is to construct biderivations (for example, see [2,6,20,21]), as shown in the following lemma. Lemma 1.2.…”
Section: Introductionmentioning
confidence: 99%
“…A mapping φ of a Lie algebra g is called commuting if [φ(x), x] = 0 for any x in g (see [2]). An important application of linear commuting mappings is to construct biderivations (for example, see [2,6,20,21]), as shown in the following lemma. Lemma 1.2.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, biderivations are closely related to the theory of commuting linear maps that has a long and rich history, and we refer to the survey [4] for the development of commuting maps and their applications. It is worth mentioning that Brešar and Zhao considered a general but simple approach for describing biderivations and commuting linear maps on a Lie algebra L that having their ranges in an L-module [6], which covered most of the results in [11,14,22,29,31], and inspires us to generalize their method to Hom-Lie algebras.…”
Section: Introductionmentioning
confidence: 99%
“…In [7], the authors determined all the skewsymmetric biderivations of W(a;b) and found that there exist non-inner biderivations. In [12,13], the authors characterized the biderivations without the anti-symmetric condition of the finite dimensional complex simple Lie algebra and some W-algebras, meanwhile, presented some classes of non-inner biderivations. In 2015, Xu and Wang generalized the notion of biderivations of Lie algebra to the super case in [16], and the authors mainly discussed some properties of super-biderivations on Heisenberg superalgebras.…”
Section: Introductionmentioning
confidence: 99%